Antropologia fotografii Zdjęcia artystów w literackim ujęciu Wisławy Szymborskiej, Zbigniewa Herberta i Andrzeja Stasiuka - Zalewski, Cezary (Przestrzenie Teorii, 2007)
The article discusses transpositions of photographs of artists contained in W. Szymborska's works Znieruchomienie [Demotioning], Z. Herbert's Pan Cogito z Marią Rasputin - próba kontaktu [Pan Cogito with Mary Rasputin - an attempt to contact] and A. Stasiuk's Jadąc do Babadag (Going to Babadag). The common feature of these three presentations consists in depriving or levelling the biographical context thanks to which general musings on human nature become possible. They lead to a conclusion on the uprooted character of human condition, which becomes deprived of its home (Stasiuk), mother country and culture (Herbert) and even corporality (Szymborska). Due to this, man appears as an unrecognisable being, possible to capture exclusively in the temporal categories.